The effect of coronavirus disease (covid-19) risk perception on behavioural intention towards untact tourism in Malaysia - Nur Azifah Sahran; Norizzaidah Ahmad Zawawi; Moony Saleney Sawan; Muhammad Syahrul Fahmy Abd Razab (2021)
In Malaysia, the effect of COVID-19 has put the tourism industry under pressure. The prolonged dissemination of the novel coronavirus had caused Malaysia to move to untact tourism. Untact is a new paradigm that accommodates individuals’ need to minimise their perceived risks. However, untact tourism caused travellers’ refusal as they perceived it negatively. In addition, not many researchers have been done in investigating traveller risk perception following health crises. Thus, this research is designed to study the impact of the perceived risk of COVID-19 on behavioural intentions towards untact tourism among Malaysian tourists. It explored cognitive, affective, and emotional perceived risk on behavioural intention towards untact tourism. This research will use a questionnaire as a method to collect the data. Data collected from this questionnaire will be analysed using SPSS. This study is believed to provide a good insight towards academicians and practitioners in preparing them to the post-corona field for a new normal after the experience of restricted living during an unprecedented pandemic.